Peran Konservasi Sumber Daya Alam Terhadap SDGs Ke 6 “Menjamin Ketersediaan dan Manajemen Air dan Sanitasi Secara Berkelanjutan”di Desa Jragung - Farikha, Rikha; T, Trimurtini (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Natural resource conservation is a form of conservation effort. Natural resources are very important for human survival, especially water sanitation. In efforts to meet water resource needs and maintain sustainability, there are several inhibiting factors, including population growth, polluted environments and unstable ecosystems around water sources. A strategy for preserving natural resources by protecting dams, rivers and forests. The research method used by researchers is a qualitative descriptive method with literature study. The results of the research state that efforts are needed to ensure that natural resources, especially sanitation and clean water, remain sustainable both now and in the future. One of these efforts is the participation of the Jragung community so that they are able to maintain clean water sanitation and conservation of natural resources, especially water sources, through participatory activities.